Developing Autonomy and Transitional Paternalism. (15th September 2016) - Tucker, Faye
Abstract: Adolescents, in many jurisdictions, have the power to consent to life saving treatment but not necessarily the power to refuse it. A recent defence of this asymmetry is Neil Manson's theory of 'transitional paternalism'. Transitional paternalism holds that such asymmetries are by‐products of sharing normative powers. However, sharing normative powers by itself does not entail an asymmetry because transitional paternalism can be implemented in two ways. Manson defends the asymmetry‐generating version of transitional paternalism in the clinical context, arguing that it maximizes respect for adolescent autonomy. This article offers an alternative argument in favour of the asymmetry‐generating form of transitional paternalism, one that makes appeal to obligations that individuals have to develop self‐governance in others. We should share normative powers asymmetrically in the clinical context for three reasons. First, the asymmetric version of transitional paternalism takes seriously duties to support adolescents' developing autonomy, alongside other duties that adults have to young people. It does so by enabling young people to be involved in important decisions that they would otherwise be excluded from. This is of value because participation of this sort is central to the cultivation of their self‐governance. Second, only the asymmetric version gives young people a voice in respect of all clinical actions, and only the asymmetric version leaves open the possibility that the coarse lines of legislation might be 'fine‐tuned' in individual cases. Third, the asymmetric sharing of normative powers is consistent with the kind of social arrangements that best support autonomy.